Changes in Glycemic Control and Quality of Life in Pediatric Type 1 Diabetics with Continuous Subcutaneous Insulin Infusion of Insulin Aspart Following Multiple Daily Injection Therapy - Kawamura, Tomoyuki (The Japanese Society for Pediatric Endocrinology, 2008)
The efficacy of continuous subcutaneous insulin infusion (CSII) of the rapid-acting insulin analogue, insulin aspart, was evaluated in 26 patients with childhood-onset type 1 diabetes aged between 6 and 18 yr who had been on basal-bolus therapy (multiple daily injection (MDI) of regular human insulin or rapid-acting insulin and intermediate/long-acting insulin). The glycemic control in the patients was evaluated based on changes in the clinical parameters and the patient quality of life (QOL) was evaluated by using the insulin therapy-related QOL questionnaire. Twenty two patients continued CSII during the 6-mo study period. The mean HbA1c was 7.8 ± 1.8% at baseline and it decreased to 7.4 ± 0.8% at 6 mo after the start of the CSII. Overall, no decrease of the QOL post-CSII initiation was noted. The possible superiority of CSII as compared to MDI was suggested for patients who “eat out” or “have to look for an appropriate place for insulin injection.” Aside from an inadequate indwelling needle placement detected after the initiation of CSII in several patients, no adverse event associated with NovoRapid(®) was seen. In conclusion, CSII of rapid-acting insulin appears to be a useful therapy for patients with childhood-onset type 1 diabetes.